Treatment with HMGB1 inhibitors diminishes CTL-induced liver disease in HBV transgenic mice. - Sitia, G; Iannacone, M; Müller, S; Bianchi, M; Guidotti, L (2007)
Using hepatitis B virus (HBV) transgenic mice as recipients of virus-specific cytotoxic T lymphocytes (CTLs), we recently showed that polymorphonuclear neutrophils (PMNs) and the matrix-degrading metalloproteinases (MMPs) they produce are necessary for the intrahepatic recruitment of antigen nonspecific mononuclear cells that amplify the liver damage initiated by the CTLs. We now report that the high-mobility group box 1 protein (HMGB1) is also involved in this process. Transfer of CTLs in HBV transgenic mice induces the translocation of HMGB1 from the nucleus to the cytoplasm of hepatocytes surrounding CTL-containing necroinflammatory liver foci, without significant net synthesis of HMGB1. Treatment of CTL-injected HBV transgenic mice with either recombinant Box-A or glycyrrhizin, two functional inhibitors of extracellular HMGB1, significantly decreases the intrahepatic recruitment of PMNs and all other inflammatory cells, in the face of intact homing of virus-specific CTLs into the liver. The inhibition of PMN chemoattraction explains the mode of action of glycyrrhizin, which has long been used in Japan for the treatment of hepatitis, and suggests that new and more potent inhibitors of HMGB1 may be useful for the treatment of patients chronically infected with HBV.